2016
DOI: 10.1111/nhs.12209
|View full text |Cite
|
Sign up to set email alerts
|

Experiences regarding maternal age‐specific risks and prenatal testing of women of advanced maternal age in Japan

Abstract: The number of pregnant women of advanced maternal age has increased worldwide. Women in this group have an increased chance of fetal abnormality. To explore Japanese women's experiences regarding maternal age-specific risks and prenatal testing, we conducted a descriptive qualitative study. Semi-structured interviews were conducted with 16 women aged 35 years or over who had given birth within the previous three months to a healthy, term infant. Thematic analysis of transcribed interview data was performed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
2
5
0
2
Order By: Relevance
“…Finally, the woman decided not to undergo prenatal testing, and she gave birth to a baby without disability. Therefore, the findings of the present study are similar to those of Murakami et al (2016), except that the participants in my study gave birth to babies with disabilities-thus the consequences of the doctors' comments were more serious. Furthermore, participants in the present study reported on some doctors who did not provide information about the babies' disabilities despite having diagnosed them.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Finally, the woman decided not to undergo prenatal testing, and she gave birth to a baby without disability. Therefore, the findings of the present study are similar to those of Murakami et al (2016), except that the participants in my study gave birth to babies with disabilities-thus the consequences of the doctors' comments were more serious. Furthermore, participants in the present study reported on some doctors who did not provide information about the babies' disabilities despite having diagnosed them.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, one mother reported that she was "accused" by the doctor for asking about prenatal testing. A very similar case was reported by Murakami et al (2016), who investigated the experiences of prenatal testing among Japanese women who gave birth to babies without disability at age 35 years or older. In that study, a 37-year-old woman asked the doctor about prenatal testing, and the doctor actively discouraged the woman from having the test.…”
Section: Discussionsupporting
confidence: 66%
“…Zunächst löst die Konfrontation mit dem Altersrisiko insbesondere aufgrund der fehlenden Kenntnisse Emotionen aus. Überraschung und Besorgnis oder auch stärkere Gefühle, wie Schock und Angst werden beschrieben [35,38,39]. Strategien, um diese Bedrohung zu handhaben, bestehen in einem individuellen Informationsmanagement, dem Bedürfnis nach Kontrolle, guter Vorbereitung, Ablenkung von Gedanken über Risiken, emotionaler Distanz zur Schwangerschaft und der Relativierung von Risikozuschreibungen [30,32,35,[37][38][39][40].…”
Section: Strategien Im Umgang Mit Der Altersrisikozuschreibungunclassified
“…Sie werden zu Expertinnen in eigener Sache und erleben, wie sich mit der Suche nach Informationen Gefühle der Überforderung ein-stellen, die das emotionale Wohlbefinden beeinträchtigen. Das japanische Sample bei Murakami et al [38], welches zu ihrem Erleben der pränatalen Diagnostik befragt wurde, beschreibt Ambivalenzen gegenüber der Beschaffung von Informationen, da diese die Sorgen verstärken können. Sie verlassen sich darauf, dass ihre Ärztinnen notwendige Themen ansprechen, wobei in Japan keine ärztliche Informationspflicht über die pränatale Diagnostik besteht.…”
Section: Strategien Im Umgang Mit Der Altersrisikozuschreibungunclassified
“…Information has been identified as a vital tool in combatting health challenges facing women in the developing-world (Nwagwu & Ajama, 2011;Ezema & Ugwuanyi, 2014;Murakami et al, 2015) and in improving women's reproductive health (Martin, 1996;Thapa, 1996). Martin (1996, p. 181) found that "most of the unnecessary deaths and disease burden could be prevented through application of low-cost effective technologies in medical care and provision of health information to parents and child care-takers".…”
Section: Reproductive Health Information Access Among Rural Women In mentioning
confidence: 99%